The new institutional economics: applications for agricultural policy research in developing countries - Kherallah, Mylene; Kirsten, Johann F. (International Food Policy Research Institute, 2001)
This paper summarizes the potential contributions of the new institutional economics to agricultural policy research, with particular emphasis on developing countries. The paper provides an overview of the new institutional economics and its several branches of thought. It then describes the future challenges facing world agriculture and shows the potential applications of new institutional and transaction costs economics to agricultural policy analysis in this new world environment. The paper concludes by providing specific examples of interest in the area of agricultural market research in developing countries that can be analyzed using the new institutional economics.